'This is What I go Through': Latinx Youth Facultades in Suburban Schools in the Era of Trump. Issue 7 (10th November 2022) - Rodriguez, Gabriel; González Ybarra, Mónica
ABSTRACT: This qualitative study examines reflections of 11 Latinx youth in Illinois and Colorado in their predominantly White, suburban high schools. We center the experiences and perspectives of Latinx youth, as we stand to gain insights into how they perceive their schools prepared and impacted their engagement for civic life. We highlight how youth from two distinct schools share similar reflections about their high school experiences and muddled approaches for civic life. We draw upon Gloria Anzaldúa's notion of facultad to examine how these particular youth engage their instincts, knowledge, and sensibilities to survive predominately White educational contexts. We then bring together literature that responds to the question about the role of schools and preparing young people to be engaged in sociopolitical discussions and action.